The Decline of Child Sexual Abuse in Canada: Evidence From the 2014 General Social Survey. (September 2019) - Shields, Margot; Tonmyr, Lil; Hovdestad, Wendy E.
Objective: To provide evidence of trends in child sexual abuse (CSA) in Canada. Methods: Using data from 15, 801 males and 18, 669 females who responded to the 2014 General Social Survey (GSS), we compared the prevalence of CSA by age cohorts. Age cohort patterns were examined for several sub-populations including males, females, Indigenous peoples, and people living in low-income households. Results: After an increase in the post-World War II period, there has been a decline in CSA in Canada since the early 1990s. Findings indicate a decline for both sexes; although, the evidence is more compelling for females. There is also evidence of a decline for Indigenous peoples, for those living in low-income households, and regardless of the relationship to the perpetrator (i.e., family member, a teacher/professor/tutor, a babysitter, a nanny, other non-family member but known to the respondent, or a stranger). Conclusions: In Canada, evidence from 3 retrospective population surveys suggests a decline in CSA since the early 1990s. However, given the associated harm, continued progress to the eradication of CSA is essential.